The Effects of Robotics on Fully Residential School Students’ Science Process Skills - Ibrahim, Hafzan; Bilal Ali, Mohamad; Aliah Phang Abdullah, Fatin; Abu Samah, Norazrena (International Journal of Psychosocial Rehabilitation, 2020)
Recently, using robotics in school education as innovation in learning and instructional for teaching purpose has become one of the main concerns among researchers. Robotics in education provides a way of learning that seems to be particularly attractive to students who are struggling with conventional school methods. Therefore, this research proposes an approach to use robotics as a tool to enhance science process skills which is one component of scientific skills. As a result, research related to the Quality Answers SPM in Physics in Malaysian Certificate of Education student which show the level of students' achievement is low. The aim of this study is to investigate the impact of using robotics in science process skills among Fully Residential School student. In this research, constructivist methodologies for integrating robotics in kinematics in Physics class are suggested. The instrument used in this study is Integrated Process Skills Test II, a paper and pencil multiple-choice test to measure the acquisition of the integrated science process skills. This paper explains how the robotics positively changed the effect. Thus, efforts to increase the level of science process skills should be taken to produce individual who are excellent in Science and Mathematics.